2019
DOI: 10.1108/ijlss-01-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Lean Six Sigma effect on Jordanian pharmaceutical industry’s performance

Abstract: Purpose This study aims to investigate the effect of Lean Six Sigma elements on the Jordanian Pharmaceutical Manufacturing organizations’ business performance. Design/methodology/approach Data were collected from 120 managers out of about 300 managers by means of questionnaire. After confirming normality, validity and reliability of the study tool, correlation analysis was carried out, and then multiple regressions were used to test the hypotheses. Findings The results show that there is an agreement on hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 37 publications
2
41
0
1
Order By: Relevance
“…We know our key suppliers and try to build deep connections with their managers and decision makers [51] SP10 Our key suppliers are loyal to our firm [51] FP9 The overall growth of our firm is better than that of competitors [79] FP10 The employee satisfaction level of our firm is better than that of competitors [21] [63] Amman and they are classified into 10 industrial sectors, namely therapeutics, plastic and rubber products, chemicals, engineering and electrical industries, furniture, construction, printing and paper, food and supply, garments, and mining. As recommended by [81], the sample size that is suitable for this population is 292.…”
Section: Sp5mentioning
confidence: 99%
See 1 more Smart Citation
“…We know our key suppliers and try to build deep connections with their managers and decision makers [51] SP10 Our key suppliers are loyal to our firm [51] FP9 The overall growth of our firm is better than that of competitors [79] FP10 The employee satisfaction level of our firm is better than that of competitors [21] [63] Amman and they are classified into 10 industrial sectors, namely therapeutics, plastic and rubber products, chemicals, engineering and electrical industries, furniture, construction, printing and paper, food and supply, garments, and mining. As recommended by [81], the sample size that is suitable for this population is 292.…”
Section: Sp5mentioning
confidence: 99%
“…Validity of the research instrument can be confirmed by ensuring both content and face validity [79]. To ensure content validity of the research instrument, Reliability includes internal consistency of the construct latent variables [9].…”
Section: Validity and Reliabilitymentioning
confidence: 99%
“…Meanwhile, the lean supply chain constitutes an adaptation of lean manufacturing principles as applied to supply chain activities that create value for customers by eliminating waste (Anand & Kodali, 2008). Recent competition is no longer between companies, but within the supply chain (Alkunsol, Sharabati, Al Salhi & El-Tamimi, 2018). Hence, extending lean practice to the entire supply chain is important since a company's inability to vie with competitors depends exclusively on its internal organization (Jasti & Kurra, 2017).…”
Section: Lean Supply Chainmentioning
confidence: 99%
“…Discussion centering extensively on manufacturers featured in 63.3% of articles, while that of manufacturing-related lean practice under the cGMP was the most widely featured (Houborg, 2010;Chowdary & George, 2012;Pavlović & Božanić, 2010;Jaiganesh & Sudhahar, 2013;Khlat et al, 2014). The second topic of significant concern in manufacturing is that of lean practice combined with six sigma to become lean sigma (Ismail, Ghani, Ab Rahman, Deros & Haron, 2014;Elbermawy et al, 2014;Alkunsol et al, 2018). Meanwhile, 26.7% of articles were found to focus on the lean principle as a strategic approach for healthcare service providers.…”
Section: Supply Chain Areamentioning
confidence: 99%
“…The results of implementing experience approaches were reflected in the works of (Alexander, Anthony, & Rodgers, 2017;Alkunsol, Sharabati, AlSalhi, & El-Tamimi, 2016, Deamonita, Pujiyanto, & Rosyidi, 2017Nemati, Dave, Sias, & Perkins, 2019;Kȩsek, Bogacz, & Mirza, 2019;Mousavi Isfahani, Tourani, & Seyedin, 2017;Yadav, Mathiyazhagan, & Kumar, 2017;Salam, 2008;Sigrid Nordby, 2017;Messinger, Rogers, & Hawker, 2019) analysis of which highlights one common essential point: the success of the implementation of any approaches depends on strict compliance with the conditions, the assessment of the existence and implementation of which is not subject to formalization, it is subjective, meanwhile underperformance or non-performance of these conditions are inherently flawed as a quality management system project: 1) it should be initiated by top -management of a company;…”
Section: Purpose Of the Studymentioning
confidence: 99%